A choice-based approach to the measurement of inflation expectations - Goldfayn-Frank, Olga; Kieren, Pascal; Trautmann, Stefan T. (Discussion paper, 2025)
Economists widely rely on measures of inflation expectations and uncertainty elicited via density forecasts. This method, where respondents assign probabilities to pre-specified ranges, has been subjected to criticism particularly in the recent times of high and volatile inflation. We propose a new method to elicit the full distribution of inflation expectations, which is rooted in decision theory and can be implemented in standard surveys. In two large surveys and one laboratory experiment, we demonstrate that it leads to well-defined expectations that fulfil both subjective and objective quality criteria. The method is neither perceived as more difficult nor does it take more time to complete compared to the current standard. In contrast to density forecasts, the method is robust to differences in the state of the economy and thus allows comparisons across time and across countries. The method is portable and can be applied to elicit different macroeconomic expectations.
Keywords: Graue Literatur